Hospital-Diagnosed Dementia and Suicide: A Longitudinal Study Using Prospective, Nationwide Register Data - Erlangsen, Annette (2008)
OBJECTIVE: The current study aims to examine the risk of suicide in persons diagnosed with dementia during a hospitalization and its relationship to mood disorders. DESIGN: Event-history analysis using time-varying covariates. SETTING: Population-based record linkage. PARTICIPANTS: All individuals aged 50+ living in Denmark (N = 2,474,767) during January 1, 1990 through December 31, 2000. MEASUREMENTS: Outcome of interest is suicide. Relative risks are calculated based on person-days spent in each stratum. RESULTS: A total of 18,648,875 person-years were observed during the 11-year study period. During this period, 136 persons who previously had been diagnosed with dementia died by suicide. Men and women aged 50–69 years with hospital presentations of dementia have a relative suicide risk of 8.5 (95% confidence interval: 6.3–11.3) and 10.8 (95% confidence interval: 7.4–15.7), respectively. Those who are aged 70 or older with dementia have a threefold higher risk than persons with no dementia. The time shortly after diagnosis is associated with an elevated suicide risk. The risk among persons with dementia remains significant when controlling for mood disorders. As many as 26% of the men and 14% of the women who died by suicide died within the first 3 months after being diagnosed whereas 38% of the men and 41% of the women died more than 3 years after initial dementia diagnosis. CONCLUSIONS: Dementia, determined during hospitalization, was associated with an elevated risk of suicide for older adults. Preventive measures should focus on suicidal ideation after initial diagnosis but also acknowledge that suicides can occur well after a dementia diagnosis has been established.